Compromise Effect in Food Consumer Choices in China: An Analysis on Pork Products - Wu, Linhai; Gong, Xiaoru; Chen, Xiujuan; Hu, Wuyang (Frontiers in Psychology, 2020)
As a reflection of rational consumer behavior, the compromise effect can be found in decision-making behaviors regarding consumer choice of commodities. Aside from price, food quality and safety, which are directly related to consumer health, are important factors that influence consumer behavior. To study whether the compromise effect exists in food consumer behavior, we examined consumer choice in the context of different decoy information (e.g., low price, high price, and different presentation) using traceable pork, brand pork, and geographically indicated pork. Results demonstrated that, in regard to consuming pork products, consumer behavior exhibited significant compromise effects after receiving both low-price and high-price decoy information. However, when the presentation of low-price and high-price decoy information was changed, i.e., decoy information was presented when consumers were autonomously making choices in a neutral information context, the compromise effect was weakened, and consumer preferences changed systematically, thus suggesting the existence of an anchoring effect. This study highlights the implications of the compromise effect in food marketing and policies related to food safety.